The Effect of Macro-Particle Blocking Plate on the Morphology of Coated CrN Film by Arc Cathodic Evaporation Method - Trinh, Van Trung (JST: Engineering And Technology For Sustainable Development, 2021)
Macro-particles often have a negatively affect on the properties of the coatings fabricated by arc cathodic evaporation. To prevent these macro-particles forming on the coating, a blocking plate can be used to filter out them. Disc-shaped blocking plates with different diameters of Df influence the number of macro-particles and the deposition rate of the coating film. The structure and morphology of macro-particles and coatings were investigated by optical microscope, stereoscopic optical microscope, electron microscope, energy dispersive spectrum (EDS), and XRD spectrum. The results show that the use of a larger diameter of the blocking plate reduces the density of macro-particles but also reduces the thickness of the coating as well as deposition rate of CrN film.